Blood Donors' Age, Haemoglobin Type, G6PD Status, and Blood Group Impact Storability of CPDA-1 Banked Whole Blood: A Repeated-Measure Cohort Study in Cape Coast, Ghana. (30th May 2020) - Adu, Patrick; Kubi, Gilbert Appiah; Kumi, Amos; Gbedoho, Raphael E. K.; Kwakye, Festus Ansah; Sarpong, Emmanuel; Drai, Constantine; Dompreh, Samuel; Sersah, Fredrick Afful; Gyamerah, Eric Ofori
Abstract : Background . The high prevalence of haemoglobin variants and glucose 6-phosphate dehydrogenase disorder (G6PDd) in sub-Saharan Africa means that substantial proportions of donor blood units carry these red cell abnormalities. Aim . This study investigated the impact that inherited haemoglobin variants and/or G6PD status have on whole blood banked at 4–6°C for 35 days. Method . This repeated-measure cohort study was undertaken on 103 donor blood units collected into blood bag containing CPDA-1 anticoagulant. On days 0, 7, 14, 21, and 35, full blood count, osmotic-induced haemolysis, and plasma K+ levels were estimated. Also, on day 0, G6PD status, haemoglobin variants, % foetal haemoglobin, and blood group of donor units were determined using methaemoglobin reductase, cellulose acetate electrophoresis, modified Bekte alkali denaturation assay, and slide haemagglutination test, respectively. Result . Overall, although plasma K+ levels increased during storage, donor units from individuals ≥20 years, G6PD normal, Hb AC, or blood group B had comparatively higher percentage change in plasma K+ during storage. Osmotically induced haemolysis of donor units was significantly decreased in Hb AC (compared with Hb A or AS) donor units on days 7, 14, 21, and 35 (p < 0.0001 in each case). G6PDd donor units had comparatively reduced osmotic-induced lysis compared with G6PD normal units, reaching a statistical significance on day 35 (p = 0.043 ). Also, Hb AC units had comparatively nonstatistically higher plasma K+ at all time points (compared with Hb A or AS). Furthermore, whereas donor units from individuals ≥20 years showed significantly higher median free haemoglobin on day 21 (compared to donor <20 years), when donor units were stratified per Hb variants, only Hb AS units had median free haemoglobin below the 0.8% threshold after 35 days' storage. Conclusion . Age of donor, blood group, Hb AC variant, and G6PD status may be important considerations in the storability of whole blood.